Storm-time equatorial thermospheric dynamics and electrodynamics - Navarro Dominguez, Luis A. (2020)
It presents the first comprehensive study of the equatorial thermospheric dynamics and ionospheric electrodynamics over Peru following enhanced energy depositions into the high-latitude ionosphere during geomagnetic storms. We used extensive observations of ionospheric plasma drifts and of night-time thermospheric neutral winds from the Jicamarca Incoherent Scatter Radar and from the network of Fabry-Perot Interferometers deployed in the central region of Peru respectively.